Expressive writing. A tool to help health workers of palliative care - Tonarelli, Annalisa; Cosentino, Chiara; Tomasoni, Cristina; Nelli, Liliana; Damiani, Ilaria; Goisis, Stefano; Sarli, Leopoldo; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2018)
Background and aims: From a previous study (1) was highlighted that Expressive writing is an important strategy for preventing and managing the effects of compassion fatigue (2). It helps educate caregivers in recognising these feelings and providing them with a “space” and a time for their reflection. This, in turn, results in significant positive repercussions on the quality of service, reducing burnout risk, implementing coping strategies, and increasing perceived work satisfaction. Reflecting occasionally in writing about ambiguous and emotionally charged situations helps in many ways: it facilitates clarification and problem-solving, and makes one more spontaneous and present in social situations, more in tune with others and available to interact. People begin to interact differently with others and see themselves in a new light after writing about an emotional subject. The objective of thi study is ascertain and confirm the results of the previous study using a reduced methodological approach. Infact, the difference from the previous research is the use of only two expressive writing sessions. Methods: A comparison was made between the expressive writing and neutral writing of two randomized groups of health care professionals of palliative care. They were evaluated pre- and post-intervention using several scales and an ad hoc questionnaire. Results: After analyzing the texts, this study confirm  previous results, using only two sessions.